Penalty Standards for Sexual Harassment Offences in Unionized Workplaces - Taylor, K. Wayne (Relations industrielles / Industrial Relations, 1998)
To identify penalty standards in use for sexual harassment in unionized workforces, 54 arbitrations of grievances against penalties assigned for sexual harassment in Canada between 1985-1995 were examined. The standard penalty for sexual harassment involving sexual assault or language and touching is termination. The standard penalty for sexual harassment involving touching (without language) and language (without touching) is suspension. Standard penalties are varied under a number of conditions. Management can use these standards as guidelines for assigning penalties. Unions will find the standards useful for judging the fairness of the penalty assigned.
Keywords: Arbitration; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Discipline; Labor Unions; Sexual harassment; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies